Knowledge Organization Systems in Canadian Digital Library Collections - Shiri, Ali (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
The paper reports on a study of the ways in which Canadian digital library collections make use of knowledge organization systems to support users’ information search behaviour. The study identified 33 digital collections which have employed some type of knowledge organization system in their search interfaces. Cet article présente les résultats d’une étude sur la manière dont les systèmes d’organisation des connaissances sont utilisés par les collections des bibliothèques numériques canadiennes, afin d’assister le comportement de recherche informationnelle des utilisateurs. Cette étude a identifiée 33 collections numériques qui ont employé certains types de systèmes d’organisation des connaissances dans leurs interfaces de recherche.